Referential and relational discourse coherence in adults and children - Gagarina, Natalia; Musan, Renate (Studies on language acquisition, 2020)
Frontmatter --Contents --Introduction --The comprehension of coherence relations in expository texts at the age of 10 and 12 --Short sentences, easy to read? Effects of connectives and layout on text comprehension by beginning readers --Explicit coherence relations in children's and adults' spoken narratives: the importance of und for the acquisition of German connectives --Text organization in typically developing bilinguals and bilinguals at risk of DLD: what is different and how language independent is it? --Referential coherence: Children's understanding of pronoun anaphora. Insights from mono- and bilingual language acquisition --Reference in French and German: A developmental perspective --The use of pronouns as a developmental factor in early Russian language acquisition --Index
"They go back to two workshops on “Text coherence und text comprehension of children and adults” at the Annual Conference of the German Linguistic Society, 23.-25.02.2011, at the University of Göttingen, and on “Cohesion and coherence in text comprehension and text production”, 26.-27.09.2013, at the University of Osnabrück." - S. 3
Keywords: Konferenzschrift -- 2011 -- Göttingen; Konferenzschrift -- 2013 -- Osnabrück; Textkohärenz; Diskurs; Erwachsener; Kind